2012
DOI: 10.4049/jimmunol.1200402
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Independent Differentiation and Maintenance of Effector-like Resident Memory T Cells in Tissues

Abstract: Differentiation and maintenance of recirculating effector memory CD8 T cells (TEM) depends on prolonged cognate antigen stimulation. Whether similar pathways of differentiation exist for recently identified tissue-resident effector memory T cells (TRM), which contribute to rapid local protection upon pathogen re-exposure, is unknown. Memory CD8αβ+ T cells within small intestine epithelium are well-characterized examples of TRM and they maintain a long-lived effector-like phenotype that is highly suggestive of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
746
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(805 citation statements)
references
References 53 publications
34
746
1
Order By: Relevance
“…DCs can provide Ag and type I IFN for CD69 induction in T cells in vitro TCR-dependent activation and exposure to various combinations of cytokines, including type I IFN, IL-33, TNF-a, and TGF-b, induce CD69 expression in T cells (7,22). Given that we observed CD69 expression by T cells in both skin epithelium and dermis, we contemplated whether DCs accumulating in these tissue compartments during infection (21) could provide the relevant Ag and/or noncognate activation signals to T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DCs can provide Ag and type I IFN for CD69 induction in T cells in vitro TCR-dependent activation and exposure to various combinations of cytokines, including type I IFN, IL-33, TNF-a, and TGF-b, induce CD69 expression in T cells (7,22). Given that we observed CD69 expression by T cells in both skin epithelium and dermis, we contemplated whether DCs accumulating in these tissue compartments during infection (21) could provide the relevant Ag and/or noncognate activation signals to T cells.…”
Section: Resultsmentioning
confidence: 99%
“…These T RM cells provide immediate local immunity (2,5,6) and, therefore, their generation holds promise for novel vaccines against pathogens that target barrier tissues, such as skin and mucosa. Although some aspects of peripheral memory formation were determined recently, such as the contributions of the cytokines TGF-b and IL-15 (3,4,7), the molecular mechanisms regulating early effector T cell retention as a prerequisite for subsequent T RM cell differentiation are not fully understood.…”
mentioning
confidence: 99%
“…CD103 mediates binding to E‐cadherin, which is expressed on epithelial cells 161. Mice lacking CD103 show defects in establishing antigen‐experienced “tissue‐resident” T cells of peripheral tissues 162. For the establishment of bone marrow‐resident memory CD4 lymphocytes, we have shown that CD69 is essential 137.…”
Section: “Tissue‐resident” Vs Bone Marrow‐resident Memory T Lymphocytesmentioning
confidence: 85%
“…Antigen is needed for the differentiation of T cells into “tissue‐resident” T cells 157, 166. They seem to play a prominent role in controlling persistent, latent infections,167 but apparently can also be maintained in the absence of antigen 162. “Tissue‐resident” memory T cells have been postulated to survive in dedicated niches providing them with distinct survival signals, such as CD103/E‐Cadherin166 or CD49a/Collagen type I and IV 168.…”
Section: “Tissue‐resident” Vs Bone Marrow‐resident Memory T Lymphocytesmentioning
confidence: 99%
“…From a mechanistic standpoint, others have shown that TGFβ production in certain tissues promotes CD103 expression, either soluble TGFβ or membrane‐bound TGFβ (Casey et al., 2012; Lee et al., 2011; Mackay et al., 2013; Yu et al., 2013). Our studies build on this foundation to demonstrate that signaling through TGFβ bound to the membrane of endometrial DCs was responsible for the induction of CD103 on naïve CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%